Role of media in the promotion of Turkish culture to young people: Research on Haci Bektaş Veli, Mevlana and Yunus Emre - Imik Tanyildizi, Nural (Ankara Haci Bayram Veli University, 2011)
The thought of individuals are shaped by values and beliefs, and become effective in social culture. The media is followed by community, affects individuals in different ways and has an important role in transferrence of feelings and thoughts. For this reason, it is also possible to say that the media is "the vehicle of the transportation of culture". Media plays an active role in the cultural structure of society and shapes this structure today. The aim of this study is to determine how effective is the media in the promotion of young people about the important building blocks of culture of Anatolian Evliyas such as Haci Bektaş Velî, Yunus Emre, Mevlana. A Questionnaire is applied to 500 university students from different provinces and selected through stratified random sampling. The obtained data was analyzed on SPSS program. This analysis shows that the media is not sufficient to introduce Turkish culture to young people.
Türk kültürünün gençlere tanitiminda medyanin rolü: Haci Bektaş Velî, Mevlana ve Yunus Emre üzeri?ne bi?r araştirma
Keywords: Effect of media; Haci Bektaş Velî; Mevlana; Promotion of culture; Turkish culture; Yunus Emre